The final stage of the laparoscopic procedure: exploring final steps - Ricardo A. Natalin; Fabio S. Lima; Thomé Pinheiro; Eugenio Vicari; Valdemar Ortiz; Cassio Andreoni; Jaime Landman (International Brazilian Journal of Urology, 2012)
Despite significant advances in laparoscopic technique and technologies, laparoscopic Urologic surgery remains technically demanding regarding various surgical steps including the challenge of specimen retrieval and extraction, whether to install a drainage system and the best option for wound closure. Laparoscopic specimen entrapment and extraction occurs at what is falsely considered the "end of the procedure". During open surgery, after the specimen has been mobilized, the specimen is simply lifted out of the larger incision which has been made to achieve the surgical objectives. In contrast, significant laparoscopic skill is required to entrap and safely extract laparoscopic specimens. Indeed, the Urologist and surgical team which are transitioning from open surgery may disregard this important part of the procedure which may lead to significant morbidity. As such, it is imperative that during laparoscopic procedures, the "end of the procedure" be strictly defined as the termination of skin closure and dressing placement. Taking a few minutes to focus on safe specimen entrapment and extraction will substantially reduce major morbidity. The following review focus on the technology and technique of specimen entrapment and extraction, on the matter of whether to install a drainage system of the abdominal cavity and the options for adequate closure of trocar site wounds. This article's primary objectives are to focus on how to minimize morbidity while maintain the advantages of a minimally invasive surgical approach.